Creating safe spaces: designing day shelters for people experiencing homelessness. Issue 1 (2nd January 2017) - Petrovich, James C.; Roark Murphy, Erin; Hardin, Laura K.; Koch, Brooke R.
ABSTRACT: Day shelter programs are an important resource for people experiencing homelessness, offering respite from inclement weather, social stigma, victimization, and access to essential services and resources. Creating functional day shelter spaces requires that staff, services, and facilities support the needs of this vulnerable and marginalized population. Little guidance, however, is available regarding the design of day shelter spaces that support service engagement and positive service outcomes. This systematic review was conducted to support the development of a new day shelter in Fort Worth, Texas, identifying and reviewing interdisciplinary resources relevant to the design of these facilities. Based on the review, a preliminary taxonomy emphasizing day shelter client safety, security, dignity and health and well-being is proposed. Additional discussion identifies practical considerations affecting the implementation of the taxonomy, design priorities, and how the taxonomy was applied to the design of the Fort Worth day shelter.